2022
DOI: 10.3390/healthcare11010134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Psychological Impact of COVID-19 on Self-Employed Private Healthcare Workers with Respect to Employed Public Healthcare Workers: Three-Wave Study during the COVID-19 Pandemic in Spain

Abstract: (1) Background: Coronavirus disease, also called COVID-19, is a worldwide pandemic with a major impact on all aspects of the individual (health status, psychological, and economic aspects, among others). The perception of health professionals in this situation has been influenced by their economic and psychosocial situations. On the economic level, self-employed workers have no state subsidies, with the added disadvantage of not having sufficient means to cope with contagion. This could potentially have an imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Differences between public and private healthcare sectors has been also analyze previously. According to a recent study by Pabón-Carrasco, HCWs employed in publicly healthcare institutions reported a lower perceived risk of COVID-19 transmission compared to their counterparts in private institutions during the first wave 43 . However, anxiety levels were higher in public employed HCWs compared to those reported by those privately employed (more than 25% and ~ 20%, respectively).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Differences between public and private healthcare sectors has been also analyze previously. According to a recent study by Pabón-Carrasco, HCWs employed in publicly healthcare institutions reported a lower perceived risk of COVID-19 transmission compared to their counterparts in private institutions during the first wave 43 . However, anxiety levels were higher in public employed HCWs compared to those reported by those privately employed (more than 25% and ~ 20%, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…However, anxiety levels were higher in public employed HCWs compared to those reported by those privately employed (more than 25% and ~ 20%, respectively). Both groups had high levels of anxiety, despite private sector was not considered first-line 43 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations